The Microbiomes of Pancreatic and Duodenum Tissue Overlap and Are Highly Subject Specific but Differ between Pancreatic Cancer and Noncancer Subjects - Del Castillo, Erika; Meier, Richard; Chung, Mei; Koestler, Devin C; Chen, Tsute; Paster, Bruce J; Charpentier, Kevin P; Kelsey, Karl T; Izard, Jacques; Michaud, Dominique S (Cancer epidemiology, biomarkers & prevention, 2019)
In mice, bacteria from the mouth can translocate to the pancreas and impact pancreatic cancer progression. In humans, oral bacteria associated with periodontal disease have been linked to pancreatic cancer risk. It is not known if DNA bacterial profiles in the pancreas and duodenum are similar within individuals. Tissue samples were obtained from 50 subjects with pancreatic cancer or other conditions requiring foregut surgery at the Rhode Island Hospital (RIH), and from 34 organs obtained from the National Disease Research Interchange. 16S rRNA gene sequencing was performed on 189 tissue samples (pancreatic duct, duodenum, pancreas), 57 swabs (bile duct, jejunum, stomach), and 12 stool samples. Pancreatic tissue samples from both sources (RIH and National Disease Research Interchange) had diverse bacterial DNA, including taxa typically identified in the oral cavity. Bacterial DNA across different sites in the pancreas and duodenum were highly subject specific in both cancer and noncancer subjects. Presence of genus was significantly higher in noncancer subjects compared with cancer subjects and the relative abundance of spp., previously associated with colorectal cancer, was higher in cancer subjects compared with noncancer subjects. Bacterial DNA profiles in the pancreas were similar to those in the duodenum tissue of the same subjects, regardless of disease state, suggesting that bacteria may be migrating from the gut into the pancreas. Whether bacteria play a causal role in human pancreatic cancer needs to be further examined. Identifying bacterial taxa that differ in cancer patients can provide new leads on etiologically relevant bacteria.